(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
This study was carried out in Alsiyahii area– Babylon Province to investigate the effect of feeding Awassi lambs different ratios of concentrate: wheat straw (C: R) on rumen fermentation characteristics. Five pellets of total mixed rations (TMR) containing 30:70, 40:60, 50:50, 60:40 and 70:30 of C: R ratios were prepared and offered to lambs ad libitum. Results revealed that increasing C: R ratio was associated with a significant (P<0.01) reduction in pH, lower values of 6.60, 6.50 and 6.53 were recorded in samples of rumen liquor collected from lambs fed pellets containing C: R ratios of 50:50, 60:40 and 70:30, respectively. Those samples were also characterized with lower (P<0.01) concentration of ammonia nitrogen, 4.85, 4.45 and 4.38 mg/100 ml, and higher (P<0.01) concentration of total volatile fatty acids.